Training, Rewards, and Motivation and Their Influence on Police Performance at the Jabar Regional Police Traffic Directorate - Tobi Rizkiando; Nita Kanya; Ani Yunaningsih; Fajar Eryanto Septiawan (Pusat Riset dan Inovasi Nasional, 2025)
Optimal performance of police personnel is a crucial prerequisite for delivering effective public services, particularly in the traffic sector, which directly impacts the community. In carrying out law enforcement and public service functions, police performance serves as a benchmark for institutional success in fostering public safety and order. The West Java Regional Police Traffic Directorate, as the frontline of traffic management in the province, is expected to have personnel who are not only professional but also responsive and highly committed. In this context, continuous training, a fair reward system, and strong work motivation are considered three key factors that can drive improved field performance. To address these issues, this study adopts a quantitative approach using descriptive and path analysis techniques. Data were collected through questionnaires distributed to 100 members of The West Java Regional Police Traffic Directorate, selected using the Slovin formula. The research instruments were designed to measure respondents' perceptions of training, rewards, motivation, and performance. Each variable was analyzed both simultaneously and partially to determine its contribution to personnel performance. SThe results indicate that training, rewards, and motivation have a positive influence on police performance. Among these variables, training emerged as the most dominant factor influencing performance, followed by motivation and rewards. Furthermore, the findings suggest the presence of other influencing factors not examined in this study.